The Influence of Macroeconomic Factors on the Effectiveness of Manufacturing Company Share Prices in Indonesia: A Case Study at PT Mustika Ratu Tbk. - Satfika Kurnia Sari; Aris Soelistyo (International Journal of Science and Society, 2023)
Beauty industry sector in Indonesia can be used as a profitable investment location for both local and foreign investors. The Investment growth levels in a country can be influenced by the level of economic growth in the country concerned. The capital market is an activity that occurs in the economic market which is used for various financial instruments that have long term terms with a time span of more than 1 year. A share is a sign of participation in capital that has been invested by a person or business entity in the company concerned. Inflation itself can be said to be a a situation when the price of an item is experiencing increase that occurs continuously and also occurs globally. In general, the rupiah exchange rate is a value or can also be called the price level of a country's currency which can be measured and expressed in another country's currency. The interest rate is an interest rate that has been determined and then issued by Bank Indonesia (BI) for the issuance of securities or certificates that will also be issued by Bank Indonesia. The research being carried out also has a goal, namely to be able to analyze the independent variables, namely inflation, the rupiah exchange rate and interest rates which can influence the dependent variable, namely the share price of the company PT Mustika Ratu Tbk. The method that can be used is Ordinary Least Squares (OLS). Data processing results show that this inflation rate variable can influence, but not significantly, the level of share prices in PT Mustika Ratu Tbk. The rupiah exchange rate has a significant effect influence on the share price of PT Mustika Ratu Tbk. The interest rate variable has no influence on the share price of PT Mustika Ratu Tbk.